Digital Voting Systems and Communication in Classroom Lectures: - an empirical study based around physics teaching at bachelor level at two Danish universities. Issue 1 (11th February 2015) - Mathiasen, Helle
Studies on the use of digital voting systems in large group teaching situations have often focused on the "non-anonymity" and control and testing functions that the technology provides. There has also been some interest in how students might use their votes tactically to gain "credits". By focusing on an empirical study of students' experiences with digital voting systems in lectures at two Danish universities, this study considers the premises and the contexts surrounding this technology. It will also aim to show that for both instructors and students, digital voting systems are a much broader resource than simply a device for facilitating "non-anonymity", test, control and allocation of credits. The case studies showed, for instance, that digital voting systems can be conducive to a more open approach in which the systems are used as communication tools and teaching resources in situations where feedback is important, as well as to the more widely recognized controlled approach. According to the students, digital voting systems do present the instructors with challenges. Some of these are discussed along with the students' suggestions for further development of digital voting systems' usage in lessons. The overall hope is that this case-based Danish perspective, which is viewed through a systems theory lens, can contribute to the pedagogical discussion surrounding the use of digital voting systems and provide a springboard for further research in this area.